An effect of binary fluid on the thermal performance of pulsation heat pipe - Barrak, Anwar S.; Ali, Nawfal M.; Ali, Hussein Hayder Mohammed (Zielona Góra: Uniwersytet Zielonogórski)
A pulsation heat pipe is an efficient heat pipe used in many engineering applications. This study aims to test the effect of working fluids on the thermal performance of pulsation heat pipe. Seven turned pulsation heat pipes were designed and manufactured from a copper pipe with a 3.5 mm inner diameter.
Keywords: binary fluid; oscillation heat pipe; two phase flow; thermal resistance; heat transfer